2020
DOI: 10.1128/jcm.00135-20
|View full text |Cite
|
Sign up to set email alerts
|

Practical Comparison of the BioFire FilmArray Pneumonia Panel to Routine Diagnostic Methods and Potential Impact on Antimicrobial Stewardship in Adult Hospitalized Patients with Lower Respiratory Tract Infections

Abstract: Lower respiratory tract infections, including hospital-acquired and ventilator-associated pneumonia, are common in hospitalized patient populations. Standard methods frequently fail to identify the infectious etiology due to the polymicrobial nature of respiratory specimens and the necessity of ordering specific tests to identify viral agents. The potential severity of these infections combined with a failure to clearly identify the causative pathogen results in administration of empirical antibiotic agents ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
128
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(160 citation statements)
references
References 40 publications
(64 reference statements)
25
128
1
6
Order By: Relevance
“…A recent study of the BioFire FilmArray Pneumonia panel concluded that the panel could also allow antibiotic adjustment in 71% of cases including discontinuation or de-escalation in 48% of patients. ( Buchan et al, 2020 ) These findings, particularly the utility of a rapid diagnostic test for antibiotic de-escalation, were similar to the findings in our study of the LRT Panel. The two panels have important differences.…”
Section: Discussionsupporting
confidence: 88%
“…A recent study of the BioFire FilmArray Pneumonia panel concluded that the panel could also allow antibiotic adjustment in 71% of cases including discontinuation or de-escalation in 48% of patients. ( Buchan et al, 2020 ) These findings, particularly the utility of a rapid diagnostic test for antibiotic de-escalation, were similar to the findings in our study of the LRT Panel. The two panels have important differences.…”
Section: Discussionsupporting
confidence: 88%
“…As expected, implementation of FAPP shortened the delay in getting results (4 h 15 min on average, one ICU setting being located 10 km away from the laboratory vs. 64-70 h with culture). In accordance with recent evaluations (Lee et al, 2019;Buchan et al, 2020;Murphy et al, 2020;Yoo et al, 2020), FAPP increased the positivity rate of diagnostic testing (81.6% for BAL DS , and 75.6% for ETA DS ), enabling identification of additional bacteria in 39.5% BAL DS and 37.8% ETA DS . The most common pathogens detected were consistently the same across both methods (i.e., in order of prevalence, H. influenzae, S. aureus, E. coli, S. pneumoniae, and K. pneumoniae).…”
Section: Discussionsupporting
confidence: 85%
“…However, in the same manner as for H. influenzae, discrepant results obtained for S. aureus in 7 patients (FAPP-positive but culture-negative), were not always explained by no bacterial growth. As noted previously, these findings pointed the limits of bacterial cultures, which are subject to interpretation and based on selection of dominant species assigned to play a pathogenic role, the minority species being not considered (Buchan et al, 2020;Murphy et al, 2020). These results confirmed the need to inoculate selective agars for enhancing detection of specific bacteria in lower airways (Chapin and Doern, 1983;Doern and Brogden-Torres, 1992).…”
Section: Discussionsupporting
confidence: 81%
“…In representative studies, the BPFA panel detected a viral and/or bacterial potential pathogen in 47.4 to 72% of the CAP patients ( Lee et al, 2019 , Murphy et al, 2020 , Webber et al, 2020 , Buchan et al, 2020 ). The number of patients varied from 595 to 1682.…”
Section: Discussionmentioning
confidence: 99%